The influence of sorghum physiology on rhizosphere interactions and their effect on root disease - Chung, Hung Yu (University of the Free State, 2018)
This study evaluated and investigated sorghum allelopathy and its various effects on microbial populations in the rhizosphere and effect of soil-borne pathogens. The effect of sorghum allelopathic extracts on rhizosphere soil microbial activity and diversity as well as the growth and incidence of soil-borne pathogens was investigated. The effect of different sorghum genotypes on the rhizobiome, root rot and yield were also investigated. Evaluation of the allelochemical contents of 22 sorghum genotypes showed variation between the concentration of their total phenolics and sorgoleone. The highest phenolic content was genotypes BTX ARG-1 (tan plant), RTam 2566 (purple plant), RTx 436 (tan plant) and BTx 635 (tan plant) and the lowest phenolic content was genotypes S5C719-11E (purple plant) and SCAY 21 (tan plant). The highest amount of sorgoleone was produced by genotype BTx 3197 (purple plant) and the lowest was genotype Tx 2911 (red plant). Phenolic extracts of RTx 430, RTx 436, Rtam 428, SCAY 21 and sorgoleone extracts of genotype BTx 3197 were selected for further experiments. The effect of sorghum phenolic and sorgoleone extracts on eight soil-borne pathogens in vitro showed that the extracts significantly stimulated the colony diameter of most of the pathogens. Phenolic extracts of RTx 430 and RTx 436 was found to be the most stimulating against the eight soil-borne pathogens. Sorgoleone extracts was found to significantly inhibit the colony diameter of C. capsici and F. equiseti compared to the control. Microcosms investigating the direct effects of sorghum phenolic and sorgoleone extracts on soil microbial populations showed differences (< 55 % similarity) between the functional diversity of rhizosphere soils treated with phenolics and sorgoleone compared to the untreated control. Microcosms investigating effect of the extracts on soil-borne pathogens showed significant differences in leaf length, root length and root rot rating of the treated plants compared to the control. The root rot of sorghum plants inoculated with A. alternata, C. trifolii and F. thapsinum were found to be the most inhibited by the extracts and plants inoculated with A. strictum and C. capsici were found to be the least inhibited. Extracts of SCAY 21 0.5x, RTam 428 1x and sorgoleone 1x were the most inhibiting and extracts of RTx 436 0.5x and SCAY 21 1x, the least. Microcosms investigating the indirect effects of the extracts on soil- borne pathogens showed that soils previously treated with extracts were most suppressive against A. alternata and F. thapsinum and least against P. macrostoma. Soils previously treated with RTx 436 0.5x and SCAY 21 0.5x extracts were most effective in suppressing the pathogens. The rotation trial with two sorghum genotypes showed significantly higher microbial activity in soils undergoing rotation compared to monoculture and fallow. The trial also showed differences (< 84 % similarity) between soils previously planted with soybean compared to other treatments. In the 1st season, a significantly higher root mass was recorded in sorghum undergoing cowpea and dry bean rotation compared to monoculture. In the 2nd season, significantly higher root mass was recorded in sorghum undergoing soybean and dry bean rotation compared to fallow. A significantly lower (P < 0.05) yield was recorded in sorghum plants undergoing fallow and monoculture compared to other rotations. The results of this study revealed various effects of sorghum allelochemical extracts on microbial populations in the rhizosphere and soil-borne pathogens. Further research should be conducted to clarify these effects by using molecular techniques such as next generation sequencing (NGS).
Keywords: Thesis (Ph.D. (Plant Pathology))--University of the Free State, 2018; Sorghum allelochemical extracts; Sorghum allelopathy; Rhizosphere; Soil-borne pathogens